Case report: Two sisters with a germline CHEK2 variant and distinct endocrine neoplasias - Vallera, Raphaelle D.; Ding, Yanli; Hatanpaa, Kimmo J.; Bishop, Justin A.; Mirfakhraee, Sasan; Alli, Abdel A.; Tevosian, Sergei G.; Tabebi, Mouna; Gimm, Oliver; Söderkvist, Peter; Estrada-Zuniga, Cynthia; Dahia, Patricia L. M.; et al. (Frontiers in Endocrinology, 2022)
Two sisters carrying a germline CHEK2 variant are highlighted whereby possible other genetic drivers were discovered on tumor analysis. The siblings have a germline CHEK2 mutation and developed distinct endocrine tumors. One sister had pituitary adenoma and pancreatic neuroendocrine tumor (PNET). The other sibling had a pheochromocytoma (PCC). Although both pituitary adenomas and PCC have been associated with NF1 gene mutations, only the second sister with a PCC had proven germline CHEK2 along with a pathogenic somatic NF1 mutation. Unless the tumor DNA is sequenced, the real driver mutation that is causing the patient’s tumor may not be known.